The Islamic state we knew : insights before the resurgence and their implications - Shatz, Howard J.; Johnson, Erin-Elizabeth (Research report (Rand Corporation) ;, 2015)
"The group calling itself the Islamic State poses a grave threat, not just to Iraq and Syria but to the region more broadly and to the United States and its global coalition partners. A deadly and adaptive foe, the Islamic State seemed to come out of nowhere in June 2014, when it conquered Mosul. However, the Islamic State of today is the direct descendant of a group that Iraq, the United States, and their partners once fought as al-Qa'ida in Iraq and then as the Islamic State of Iraq. The wealth of publicly available information about the group indicates that the Islamic State's reemergence in 2014, and especially its methods and goals, should not have come as a surprise, although the strength and scope of that reemergence were rightfully shocking. The history considered in this report provides information known by the end of 2011 about the group's origins, finances, organization, methods of establishing control over territory, and response to airpower. Now that the Islamic State has reemerged, countering it can rely, in part, on the great deal of accumulated knowledge available. Because Iraqis and coalition forces routed the group once, the group's history can inform four components of a successful strategy against the Islamic State: degrading the group's finances, eliminating its leadership and potential leadership, creating a better strategy to hold recaptured territory, and making use of airpower"--Provided by publisher